Dissemination of corn sheller machines to increase productivity and efficiency for corn farmer associations in Wonogiri Regency - Haikal Haikal; Bambang Margono; Moch Chamim; Yudis Adhana Surya; Zulkarnaen Ryeda Febriawan; Rendi Yanwar Perdana Putra; Apri Wiyono (Community Empowerment, 2021)
Corn is a superior agricultural product for the Giri Harjo I farmer group, Girikikis Village, Giriwoyo District, Wonogiri. However, farmers process and peel corn manually, so it takes a more time and inefficient. In order to overcome this problem, this community service designed and made a corn sheller machine that was used to simplify and increase the productivity in the corn harvesting process. This service activity begins with the delivery of the corn sheller machine to the farmer group, then exposure and training on the use of the machine. Corn shelling is accomplished by inserting the corn into the sheller shaft, after which the grinding knife separates the corn kernels from the cob. The shelling test results show that this machine works well, is practical to use, is highly portable, the production process is faster, the corncobs are not damaged, and the electric power consumption is low. This machine has a 0.5 HP motor and a production capacity of 183 kg/hour for shelling corn kernels.